The Brazilian Legal Consultant as a Strategic Pillar in Importing for International Companies: The Case of Third-Party Logistics (3PL) and Compliance in the United States (Research, Society and Development, 2025)
The objective of the present study is to demonstrate how this partnership is not just a cost-reduction measure, but a lever for global competitiveness, enabling companies to navigate with greater security, efficiency, and flexibility in an increasingly volatile and demanding business environment. The rise of Brazil as a significant consumer and producer market attracts the interest of global companies, especially those based in the United States. However, the intricate Brazilian regulatory and logistical framework, often underestimated by foreign companies, presents a substantial challenge. This article analyzes the strategic role of the Brazilian Foreign Legal Consultant (FLC), focused on the import context from the US to Brazil, as an essential bridge for operational success. It examines the logistical complexity of the "Brazil Cost," the rigidity of the Brazilian Federal Revenue Service (RFB) regarding customs matters, and the burdensome tax (IPI, PIS, COFINS, ICMS) and regulatory (ANVISA, INMETRO) mosaic. The research demonstrates that the Brazilian FLC, with in-depth knowledge of domestic legislation, is crucial not only for ensuring compliance and mitigating the risk of penalties — such as fines for erroneous tax classifications — but also for optimizing costs and deadlines through the identification of special customs regimes and the management of contracts with Third-Party Logistics (3PL) providers. The FLC's expertise translates the Brazilian legal and cultural context, making them an indispensable asset for companies seeking to navigate the complexity of importing into Brazil successfully and safely.